Current status and actual need for pediatric liver transplantation in Southern Vietnam. (30th December 2015) - Nguyen, Tu Cam; Robert, Annie; Nguyen, Phuong Van Ngoc; Nguyen, Ngoc Minh; Truong, Dinh Quang; Goyens, Philippe; Reding, Raymond
Abstract: Liver transplantation (LT) has considerably improved the outcome of patients with end‐stage liver disease, especially in children. The first pediatric LT in Vietnam was performed in 2004. To assess the current need for pediatric LT in Southern Vietnam, a total of 280 patients with chronic liver disease followed at Children's Hospital 2 (Ho Chi Minh City), the only pediatric LT center in this region, were evaluated from January 2009 to June 2014. Sixty‐seven patients satisfied criteria for LT but only one transplant surgery occurred since 2009. Parental consent for LT was obtained only in 28.4% of patients. The main reasons for the small number of LTs were financial costs, far distance from home, lifelong follow‐up and treatment, and shortage of organ donors. We conclude that the current need for pediatric LT in Southern Vietnam is high. Efforts should be made to develop the liver transplant program in this developing country.